Rho-Kinase 1/2 Inhibition Prevents Transforming Growth Factor-β-Induced Effects on Pulmonary Remodeling and Repair - Wu, Xinhui; Verschut, Vicky; Woest, Manon E.; Ng-Blichfeldt, John-Poul; Matias, Ana; Villetti, Gino; Accetta, Alessandro; Facchinetti, Fabrizio; Gosens, Reinoud; Kistemaker, Loes E. M. (Frontiers in Pharmacology, 2021)
Transforming growth factor (TGF)-β-induced myofibroblast transformation and alterations in mesenchymal-epithelial interactions contribute to chronic lung diseases such as chronic obstructive pulmonary disease (COPD), asthma and pulmonary fibrosis. Rho-associated coiled-coil-forming protein kinase (ROCK) consists as two isoforms, ROCK1 and ROCK2, and both are playing critical roles in many cellular responses to injury. In this study, we aimed to elucidate the differential role of ROCK isoforms on TGF-β signaling in lung fibrosis and repair. For this purpose, we tested the effect of a non-selective ROCK 1 and 2 inhibitor (compound 31) and a selective ROCK2 inhibitor (compound A11) in inhibiting TGF-β-induced remodeling in lung fibroblasts and slices; and dysfunctional epithelial-progenitor interactions in lung organoids. Here, we demonstrated that the inhibition of ROCK1/2 with compound 31 represses TGF-β-driven actin remodeling as well as extracellular matrix deposition in lung fibroblasts and PCLS, whereas selective ROCK2 inhibition with compound A11 did not. Furthermore, the TGF-β induced inhibition of organoid formation was functionally restored in a concentration-dependent manner by both dual ROCK 1 and 2 inhibition and selective ROCK2 inhibition. We conclude that dual pharmacological inhibition of ROCK 1 and 2 counteracts TGF-β induced effects on remodeling and alveolar epithelial progenitor function, suggesting this to be a promising therapeutic approach for respiratory diseases associated with fibrosis and defective lung repair.